Analisis Faktor Faktor Kejadian Ruptur Perineum pada Ibu Bersalin di Wilayah Kerja Puskesmas Kecamatan Sobang Kabupaten Lebak Provinsi Bant - Deti Nurhayati; Nurul Husnul Lail; Yenny Aulya (Universitas Malahayati Lampung, 2023)
ABSTRACT Perineal rupture generally occurs in labor where the fetal head is born too soon, labor is not led as it should, there is scar tissue in the perineum, in labor with shoulder dystocia.. Childbirth with perineal rupture if not handled effectively causes bleeding and infection to become more severe, and in the long term can interfere with the mother's comfort in terms of sexual relations. This study aims to determine the factors of the occurrence of perineal rupture in women in labor in the working area of Puskesmas, Sobang district, Lebak, Banten province in 2022. The research design used a cross-sectional method, the population in this study were women who gave birth normally in the working area of the Sobang District Health Center, Lebak Regency. The population in this study were 149 people, while the sample was 108 people. Analysis of the relationship between the independent variables and the dependent variable using the chi square test. It is known that 45 women (41.7%) experienced perineal rupture, the results of the chi square test showed that there was a significant relationship between birth weight (p value=0.009), birth spacing (p value=0.002), husband's support (p value=0.035), and midwife support (p value=0.015) with incidence of perineal rupture in women giving birth in the working area of the Sobang sub-district health center, Lebak district, Banten province in 2022. The factors of baby's birth weight, birth spacing, husband's support and midwife's support have a significant relationship to the incidence of perineal rupture, so it is hoped that health workers can work with mothers in the delivery process and can improve the quality in providing Normal Childbirth Care (APN) to prevent it from occurring perineal rupture. Keywords : Perineal Rupture, Low Birth Weight, Birth Spacing, Husband and Midwife Support ABSTRAK Ruptur perineum umumnya terjadi pada persalinan dimana kepala janin terlalu cepat lahir, persalinan tidak dipimpin sebagaimana mestinya, terdapat jaringan parut pada perineum, pada persalinan dengan distosia bahu. Persalinan dengan ruptur perineum apabila tidak ditangani secara efektif menyebabkan pendarahan dan infeksi menjadi lebih berat, serta pada jangka waktu panjang dapat mengganggu kenyamanan ibu dalam hal hubungan seksual. Penelitian ini bertujuan untuk mengetahui faktor-faktor kejadian ruptur perineum pada ibu bersalin di wilayah kerja puskesmas kecamatan Sobang kabupaten Lebak provinsi Banten tahun 2022. Desain penelitian menggunakan metode cross sectional, yang menjadi populasi dalam penelitian ini adalah ibu bersalin normal di wilayah kerja Puskesmas Kecamatan Sobang Kabupaten Lebak. Populasi dalam penelitian ini sebanyak 149 orang, sedangkan sampelnya sebanyak 108 orang. Analisis hubungan antara variabel independen dengan variabel dependen menggunakan uji chi square. Diketahui bahwa ibu bersalin yang mengalami rupture perineum yaitu sebanyak 45 orang (41,7%), hasil uji chi square menunjukan adanya hubungan yang bermakna antara berat badan lahir bayi (p value=0,009), jarak persalinan (p value=0,002), dukungan suami (p value=0,035), dan dukungan bidan (p value=0,015)dengan kejadian ruptur perineum pada ibu bersalin di wilayah kerja puskesmas kecamatan Sobang kabupaten Lebak provinsi Banten tahun 2022. Faktor berat badan lahir bayi, jarak persalinan, dukungan suami dan dukungan bidan memiliki hubungan yang bermakna terhadap kejadian ruptur perineum, sehingga diharapkan pihak tenaga kesehatan dapat bekerjasama dengan ibu dalam proses persalinan dan dapat meningkatkan kualitas dalam memberikan Asuhan Persalinan Normal (APN) untuk mencegah terjadinya ruptur perineum. Kata Kunci : Ruptur Perineum, BBL, Jarak Persalinan, Dukungan Suami dan Bidan